Career orientation and perceived professional competence among clinical research coordinators. Issue 5 (3rd October 2019) - Rojewski, Jay W.; Choi, Ikseon; Hill, Janette R.; Ko, Yeonjoo; Walters, Katherine L.; Kwon, Sejung; McCauley, Linda
Abstract: Introduction: This study identified underlying career orientation types of clinical research coordinators (CRCs) using cluster analysis. Select career (satisfaction, engagement, and planning) and competency-related (perceived competence) information was used to identify four distinct career orientation types. Method: A web-based survey was administered to CRCs employed in one of four research institutions affiliated with a National Institutes of Health-funded Clinical and Translational Research Award (CTSA) in the southeastern USA. Each respondent completed a survey containing questions about personal background, individual attributes, perceived professional competence, and career orientation. Results: The first CRC type (35.2%) possessed a positive, knowledge-seeking orientation, characterized by high career-related scores but a conservative assessment of perceived competence. The second CRC type (18.6%) represented an optimistic and confident career orientation reflected in moderate to high scores on each of the four identifying factors. The third CRC type (27.6%) reflected an inconsistent career orientation highlighted by lowered perceived competence. The final CRC type (18.6%) reflected a disengaged orientation characterized by negative responses to all career and competence factors. Conclusion: Understanding the career orientation of CRCs can be helpful to institutional administrators and clinical investigators as they seek to support the professional development of CRCs through tailored training efforts or work-related supports. Knowledge of career orientation may also inform individual CRCs as they manage their personal career paths by assessing current levels of functioning, career-related strengths or weaknesses, and training needs.